Efficacy Profile of Intracameral Amphotericin B. The Often Forgotten Step. Issue 6 (November 2015) - Sharma, Bhavana; Kataria, Preeti; Anand, Reena; Gupta, Rachna; Kumar, Kavita; Kumar, Salil; Gupta, Richa
Abstract : Purpose: The objectives of this study were to assess visual and structural outcomes in mycotic keratitis after conventional treatment (topical and systemic antifungals) and intracameral amphotericin B (ICAMB), and to evaluate any complications. Design: This was a prospective, nonrandomized, nonblinded interventional study. Methods: This study was conducted on 104 eyes of 104 patients with fungal corneal ulcers. Patients were categorized into 2 groups: group A, who received conventional topical and systemic antifungal medications, and group B, who received ICAMB in the dose of 5 to 10 μg in 1 mL of 5% dextrose. Response to treatment was evaluated. Results of the 2 groups were compared with appropriate statistical indices. Results: The mean final visual acuity in patients in group B receiving ICAMB was 1.22 ± 0.31 logMAR units. The improvement in mean visual acuity was 1.40 ± 0.2 logMAR units. In group A, mean visual outcome was 1.25 ± 0.73 logMAR units. There was an improvement by 0.55 ± 0.30 logMAR units. Healing with varying degrees of opacification occurred in a significant number of patients (81.48%) treated with ICAMB as compared with conventional treatment ( Z = 2.24, P < 0.05). Complications, such as sloughing, occurred in significantly fewer patients treated with ICAMB as compared with conventional treatment ( Z = 2.29, P < 0.05). Conclusions: In cases of keratomycosis where response to local and systemic antifungal treatment is not evident after 7 days, ICAMB can be safely administered to prevent the progression of ulcers and the development of complications.